2011
DOI: 10.1002/chem.201100317
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Iridium Bis(carbene) Complexes for Efficient Blue Electrophosphorescence

Abstract: Five iridium bis(carbene) complexes, [Ir(pmi)(2)(pypz)] (1), [Ir(mpmi)(2)(pypz)] (2), [Ir(fpmi)(2)(pypz)] (3), [Ir(fpmi)(2)(pyim)] (4), and [Ir(fpmi)(2)(tfpypz)] (5) (pmi=1-phenyl-3-methylimdazolin-2-ylidene-C,C(2'); fpmi=1-(4-fluorophenyl)-3-methylimdazolin-2-ylidene-C,C(2'); mpmi=1-(4-methyl-phenyl)-3-methylimdazolin-2-ylidene-C,C(2'); pypz=2-(1H-pyrazol-5-yl)pyridinato; pyim=2-(1H-imidazol-2-yl)pyridinato; and tfpypz=2-(3-(trifluoromethyl)-1H-pyrazol-5-yl)pyridinato), were synthesized and their structures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(51 citation statements)
references
References 38 publications
2
48
0
1
Order By: Relevance
“…Compounds 1, 3, and 4 were synthesized according to the reported procedures [22,26]. Compound 1 was reacted with iridium trichloride hydrate (IrCl 3 ·3H 2 O) to yield the cyclometalated Ir(III) µ-chloride bridged dimer 2 with quantitative yield.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 1, 3, and 4 were synthesized according to the reported procedures [22,26]. Compound 1 was reacted with iridium trichloride hydrate (IrCl 3 ·3H 2 O) to yield the cyclometalated Ir(III) µ-chloride bridged dimer 2 with quantitative yield.…”
Section: Resultsmentioning
confidence: 99%
“…Kido et al have reported a triscarbene iridium complex‐based device with a high external quantum efficiency of 18.6% with CIE coordinates of (0.15, 0.19) 16. Earlier, we reported the synthesis of blue iridium biscarbene complexes with an N , N ′‐heteroaromatic ( N ⁁ N ) as the third ligand 17. We found that the lowest unoccupied molecular orbitals (LUMOs) and the emissive states of these iridium complexes are mainly controlled by the N ⁁ N ligand, which is in agreement with the theoretical calculation by Su et al18 The results suggest the possibility of altering the emission color of iridium biscarbene complexes over a wide range by using different N ⁁ N ligands.…”
Section: Methodsmentioning
confidence: 96%
“…However, due to the large band gap of the deep-blue emitter and the resulting high triplet energy, the number of promising compatible host materials is limited, since an even higher triplet energy is necessary for the host to ensure trapping of the exciton on the emitter. 10,11 Among possible charge-transporting units fulfilling this criterion are dibenzofurans and N-phenylcarbazoles. 12 Substituents must be attached to these materials to prevent crystallization, 13 suppress emitter aggregation, and optimize their molecular weight for vacuum deposition.…”
Section: Introductionmentioning
confidence: 99%